Quality of Work Life as a Predictor of Employee Turnover Intention - Nisa Indah Pertiwi; Yoko Jimmy Panjaitan; Fauzan Kamil Munawwar (Psikostudia : Jurnal Psikologi, 2024)
Employees who resign and leave their job can affect the running of the company and reduce efficiency. Companies need to retain employees, so they do not feel like changing jobs. Turnover Intention can be prevented by working life factors through pleasant, satisfying working conditions, and a prosperous quality of work life. These working conditions are reflected in the quality of work life in the workplace. The purpose of this research is to determine the effect of quality of work life on turnover intention of outsourcing company employees. This research was conducted using a non-experimental quantitative method on 56 employees of an outsourcing company. Quality of work measurement tools adapted quality of work life questionnaires made by Timossi et al. and turnover intention used adaptations and modification measurements from Mobley et al. The data analysis technique used a simple linear regression test. The results showed that quality of work life affects the turnover intention of outsourcing company employees. The constitutionalism aspect has the greatest influence on the quality of work life in influencing employee turnover intention. The implication of this research finding is that to prevent turnover intention, the main concern of outsourcing company management can be directed to ensure that employees are satisfied with the constitutionalism aspect of their work.Karyawan yang mengundurkan diri dan keluar dari pekerjaan dapat mempengaruhi jalannya perusahaan dan mengurangi efisiensi. Perusahaan perlu mempertahankan karyawan agar tidak merasa ingin berganti pekerjaan (turnover intention). Turnover Intention dapat dicegah dengan faktor working life melalui kondisi kerja yang menyenangkan, memuaskan, dan kualitas kehidupan kerja yang membuat sejahtera. Kondisi kerja tersebut tercermin dalam kualitas kehidupan kerja (quality of work life) di tempat kerja. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh quality of work life terhadap turnover intention karyawan perusahaan outsourcing. Penelitian ini dilakukan dengan metode kuantitatif non-eksperimental pada 56 orang karyawan sebuah perusahaan outsourcing. Alat ukur quality of work life mengadaptasi kuesioner quality of work life yang dibuat oleh Timossi et al. dan turnover intention menggunakan adaptasi dan modifikasi pengukuran dari Mobley et al. Teknik analisis data menggunakan uji regresi linier sederhana. Hasil penelitian menunjukkan bahwa quality of work life berpengaruh terhadap turnover intention karyawan perusahaan outsourcing. Aspek constitutionalism memiliki pengaruh terbesar pada quality of work life dalam mempengaruhi turnover intention karyawan. Implikasi dari temuan penelitian ini yaitu untuk mencegah turnover intention, perhatian utama pihak manajemen perusahaan outsourcing dapat diarahkan untuk memastikan bahwa karyawan merasa puas pada aspek constitutionalism pekerjaan